WHITE TARO CATTLE HOOF MORPHOMETRY IN TARO VILLAGE, TEGALLALANG DISTRICT, GIANYAR REGENCY, BALI - Yunita, Nur Intan Wulan; Susari, Ni Nyoman Werdi; Sampurna, I Putu (Buletin Veteriner Udayana, 2022)
Hooves are a very important part of the body because they are used to support body weight and walk. As in other animals, the hoof of the cow serves to protect the phalanx III os, as a place for the animal to support the ground, to support body weight, to absorb vibrations/shock when supporting when running and jumping, and to circulate blood. This research is done to determine the morphometry of white taro cattle’s hooves in Taro village, Tegallalang District, Gianyar Regency, Bali, Indonesia. The amount of samples used is 26 taro cattle (> 3 years old). Measuring tape with cm as its unit is used to measure the hooves of the front legs. Data collection was done by referring to the method used by Radiš? et al., (2012). Data collected includes length, width, and height is analysed quantiatively. To examine the difference between male and female, Independent T-test is used in the procedure analysis with SPSS program. The results of the forefoot measurements of white taro cattle obtained that the hoof height was 12.08 cm, nail width was 21.50 cm, length was 25.33 cm. While the measurement of the front hoof of a female Taro white cow, the hoof height is 7.78 cm, the nail width is 25.00 cm, and the nail length is 17.57 cm. In general, the size of the front toenails of male and female white taro cattle were not significantly different with the coefficient of variation of the forefoot hoofs of male and female white taro cattle being large, which was >20%, so the coefficient of variation of the front paws of male and female taro white cattle was not uniform.